Processes of creation and propagation of correlations in quantum many-particle systems - Gerasimenko, V. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
The communication deals with the problem of a rigorous description of the evolution of states of quantum many-particle systems by means of the correlation operators. We construct a nonperturbative solution of the Cauchy problem of the hierarchy of nonlinear evolution equations for a sequence of marginal correlation operators, which describe the processes of creation and propagation of correlations. Moreover, the mean field asymptotic behavior of the constructed marginal correlation operators is established.